A retrospective vision to investment policies for research and development in Vietnam - Long, Hoang Xuan; Tu, Nguyen Cong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The Party and the State investment policies for research and development (R&D) are seen in numerous aspects, namely: objectives of and solutions for higher investment rates, and focus on better efficient investments. In practice, however, these policies still have certain shortages. An analysis of these short aspects of the issued policies would provide hints for innovation of policies to be issued in the next period. Code: 16060501<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">